Watching you ebook A novel. - Jewell, Lisa (2018)
"Quickly and assuredly, Jewell builds an ecosystem of countervailing suspicions...Tricky, clever, unexpected." — New York Times Book Review "Brace yourself as Jewell stacks up the secrets, then lights a long, slow fuse." — People "A seize-you-by-the-throat thriller and a genuinely moving family drama." —A.J. Finn, #1 New York Times bestselling author of The Woman in the Window The instant New York Times and #1 Sunday Times bestselling author of the None of This Is True delivers another suspenseful page-turner about a shocking murder in a picturesque and well-to-do English town, perfect "for fans of Gone Girl, The Girl on the Train, and Luckiest Girl Alive" ( Library Journal). You're back home after four years working abroad, new husband in tow. You're keen to find a place of your own. But for now, you're crashing in your big brother's spare room. That's when you meet the man next door. He's the head teacher at the local school. Twice your age. Extraordinarily attractive. You find yourself watching him. All the time. But you never dreamed that your innocent crush might become a deadly obsession. Or that someone is watching you . In Lisa Jewell's latest "bone-chilling suspense" ( People ), no one is who they seem—and everyone has something to hide. Perfect for fans of Gillian Flynn and Ruth Ware, Watching You will keep you guessing as "Jewell teases out her twisty plot at just the right pace" ( Booklist , starred review) until the startling revelations on the very last page.